Efektifitas Pengarusutamaan Moderasi Beragama pada Penyuluh Agama Islam Non PNS di Kabupaten Kendal - Vita Santa Chrisantina (Jurnal Edutrained : Jurnal Pendidikan dan Pelatihan, 2022)
Religious moderation is one of the priority programs from Religious Affair Ministry, so this study was conducted to describe and analyze the effectiveness of mainstreaming religious moderation on non-civil servant Islamic instructors in Kendal Regency and analyze the methods of mainstreaming that are adapted to the characteristic of non-civil servant Islamic instructors. This research was conducted with a pre-experimental design approach of one group pretest-posttest type. This research was conducted on a survey of 145 non-civil servants Islamic instructors in Kendal Regency. The results of this study indicate that the value of NGain at the socialization stage of religious moderation is less effective and quite effective, this is because the extension agent already knows the material so that the socialization provided does not have a significant impact on the extension worker. In terms of method used for mainstreaming religious moderation by means of socialization, it must be adapted to the knowledge condition of the non-civil servant Islamic instructors and the socialization is carried out with tiered material because the discussion of religious moderation is complex. Conclusion: it is necessary to measure the homogeneity of target knowledge before conducted socialization.